Sams teach yourself PHP, MySQL and Apache : all in one - Meloni, Julie C. (Indianapolis, Indiana : Sams Publishing, 2008)
Explains how to create Web sites using the PHP scripting language, the MySQL database system, and the Apache Web server on a Windows or Linux system.
Includes index.
Keywords: Apache (Computer file : Apache Group)